DEVELOPMENT OF DIGITAL HISTORICAL COMIC MEDIA TO IMPROVE LEARNING INTEREST OF GRADE XI 4 STUDENTS AT STATE SENIOR HIGH SCHOOL 1 PORONG : Pengembangan Media Komik Digital Sejarah Untuk Meningkatkan Minat Belajar Siswa Kelas XI 4 di SMA Negeri 1 Porong - J. Priyanto Widodo; Satrio Wibowo; Mila Dwi Karinah (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to develop a comic of the battle of November 10, 1945 in Surabaya as a learning media in the form of a digital historical comic to increase the learning interest of class XI 4 students at SMA Negeri 1 Porong. The research method used is a development research that uses five stages, namely analysis, design, development, implementation, and evaluation known as the ADDIE development model. Based on the final results of the study, it is shown that the digital comic learning media of the history of the battle of November 10, 1945 in Surabaya is suitable for use in learning. With the following results: 1) the digital comic of the history of the battle of November 10, 1945 in Surabaya is rated